Tokyo Twilight - Ozu, Yasujiro; Atsuta, Yûshun; Arima, Ineko; Fujiwara, Kamatari; Hara, Setsuko (Tartan Video, 2006)
Takako (Setsuko Hara) and Akiko (Ineko Arima) are two sisters, raised alone by their father Mr Sugiyama (Chishu Ryu) after their mother walked out on them many years ago. The broken family unit has had an unfortunate affect on both women. Takako is married to Numata, with a young daughter, but her husband drinks a lot and it is an unhappy marriage. Takako has temporarily moved back to with her father, who blames himself for arranging the marriage. Akiko is not married, but leads a rather dissolute life hanging around late-night bars and gambling houses looking for her boyfriend Keiji. At a mah-jong parlour, she meets a woman who claims to know her as a neighbour in the district they grew up as children, but she suspects the woman might be the mother who left them when she was only three years old. Touching on issues such as alcoholism, mothers abandoning children and unwanted pregnancies, Ozu’s concern in "Tokyo Twilight" is not so much the social issues they give rise to, as the affect they have on the family unit. If that message is a little too heavy-handed and obvious here, lacking the complexity of his finer work, formally "Tokyo Twilight" it is as strong as any Ozu film, with superb compositions and performances, maintaining a subdued, even languid tone throughout. [www.dvdtimes.co.uk]
Keywords: DVD-Video